Neo/adjuvant therapy in upper tract urothelial carcinoma - (:unkn) unknown (ELSEVIER SCIENCE BV, 2007)
Objectives: Urothelial carcinoma of the renal pelvis and ureter is a relatively uncommon malignancy. The majority of patients present at a stage in which disease has not penetrated through the muscularis (Tis-T2). These patients are generally treated with radical nephroureterectomy or with renal-sparing procedures in select patients, and overall the prognosis is favorable in this group. However, in patients in whom disease has spread beyond the muscularis and involved adjacent tissues, organs, or lymph nodes, the prognosis is significantly worse, making it important to consider adjuvant or neoadjuvant therapy. Methods: Literature search using PubMed was conducted to identify the related articles that formed the basis of this review. Results: The role of adjuvant external beam radiotherapy in improving local control and survival is unclear both because of the limited number of patients and because of the contradictory results of different studies. Neoadjuvant chemotherapy and concurrent cisplatin administration during radiotherapy appears as an important factor in terms of survival at 5 yr. Similarly, available data in the literature indicate that neo/adjuvant systemic chemotherapy after nephroureterectomy may provide therapeutic benefit in patients with invasive transitional cell carcinoma of the upper urinary tract. Conclusions: Adjuvant radiation therapy after radical upper urinary tract surgery has no impact upon clinical outcome, whereas systemic adjuvant or neoadjuvant chemotherapy does provide significantly better oncologic results. (c) 2007 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: upper tract; urothelial neoplasms; adjuvant; neoadjuvant; TRANSITIONAL-CELL-CARCINOMA; UPPER URINARY-TRACT; COOPERATIVE-ONCOLOGY-GROUP; RENAL PELVIS; PROGNOSTIC-FACTORS; ADJUVANT RADIOTHERAPY; URETER; SURVIVAL; CHEMOTHERAPY; CANCER